1r-2+1r2-7r+10=6r-2

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 10 and whose sum is -7.

-5,-2

Write the factored form using these integers.

1r-2+1(r-5)(r-2)=6r-2

1r-2+1(r-5)(r-2)=6r-2

Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.

r-2,(r-5)(r-2),r-2

The LCM is the smallest positive number that all of the numbers divide into evenly.

1. List the prime factors of each number.

2. Multiply each factor the greatest number of times it occurs in either number.

The number 1 is not a prime number because it only has one positive factor, which is itself.

Not prime

The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.

1

The factor for r-2 is r-2 itself.

(r-2)=r-2

(r-2) occurs 1 time.

The factor for r-5 is r-5 itself.

(r-5)=r-5

(r-5) occurs 1 time.

The factor for r-2 is r-2 itself.

(r-2)=r-2

(r-2) occurs 1 time.

The LCM of r-2,r-5,r-2,r-2 is the result of multiplying all factors the greatest number of times they occur in either term.

(r-2)(r-5)

(r-2)(r-5)

Multiply each term in 1r-2+1(r-5)(r-2)=6r-2 by (r-2)(r-5) in order to remove all the denominators from the equation.

1r-2⋅((r-2)(r-5))+1(r-5)(r-2)⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

Simplify 1r-2⋅((r-2)(r-5))+1(r-5)(r-2)⋅((r-2)(r-5)).

Simplify each term.

Cancel the common factor of r-2.

Cancel the common factor.

1r-2⋅((r-2)(r-5))+1(r-5)(r-2)⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

Rewrite the expression.

r-5+1(r-5)(r-2)⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

r-5+1(r-5)(r-2)⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

Cancel the common factor of (r-2)(r-5).

Factor (r-2)(r-5) out of (r-5)(r-2).

r-5+1(r-2)(r-5)(1)⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

Cancel the common factor.

r-5+1(r-2)(r-5)⋅1⋅((r-2)(r-5))=6r-2⋅((r-2)(r-5))

Rewrite the expression.

r-5+1=6r-2⋅((r-2)(r-5))

r-5+1=6r-2⋅((r-2)(r-5))

r-5+1=6r-2⋅((r-2)(r-5))

Add -5 and 1.

r-4=6r-2⋅((r-2)(r-5))

r-4=6r-2⋅((r-2)(r-5))

Simplify 6r-2⋅((r-2)(r-5)).

Cancel the common factor of r-2.

Cancel the common factor.

r-4=6r-2⋅((r-2)(r-5))

Rewrite the expression.

r-4=6⋅(r-5)

r-4=6⋅(r-5)

Apply the distributive property.

r-4=6r+6⋅-5

Multiply 6 by -5.

r-4=6r-30

r-4=6r-30

r-4=6r-30

Move all terms containing r to the left side of the equation.

Subtract 6r from both sides of the equation.

r-4-6r=-30

Subtract 6r from r.

-5r-4=-30

-5r-4=-30

Move all terms not containing r to the right side of the equation.

Add 4 to both sides of the equation.

-5r=-30+4

Add -30 and 4.

-5r=-26

-5r=-26

Divide each term by -5 and simplify.

Divide each term in -5r=-26 by -5.

-5r-5=-26-5

Cancel the common factor of -5.

Cancel the common factor.

-5r-5=-26-5

Divide r by 1.

r=-26-5

r=-26-5

Dividing two negative values results in a positive value.

r=265

r=265

r=265

The result can be shown in multiple forms.

Exact Form:

r=265

Decimal Form:

r=5.2

Mixed Number Form:

r=515

Solve for r 1/(r-2)+1/(r^2-7r+10)=6/(r-2)